1979
DOI: 10.1021/j100471a023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rate constants for reactions of hydrogen atoms with chlorine, fluorine, iodine chloride, and chlorine fluoride

Abstract: The infrared emission intensities from the HC1 and HF products have been used to assign relative rate constants for the reaction of H atoms with Cl2, F2, GIF, and IC1. The experiments were done in a fast flow apparatus utilizing ~1 torr of Ar carrier gas. The vibrational distributions obtained from analysis of the chemiluminescence recorded with a Fourier transform spectrometer at the first window of the flow reactor were very close to the initial distributions produced by the chemical reaction. Except for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 2 publications
5
23
1
Order By: Relevance
“…k 3(H) /k 3(D) \ 2.07È1.41 This isotope e †ect can be understood in a similar way as for reactions (1) and (2). Here, the energy barriers (e.g., 0.42 *V a G and 0.59 kcal mol~1 for reaction (3) with H and D respectively, at T \ 0 K) are very important. Transmission coefficients follow an opposite direction (e.g., i 3(H) /i 3(D) \ 0.46È1.00 within the range 150È1000 K) and the mass e †ect is negligible.…”
Section: Variational Transition State Thermal Rate Constantsmentioning
confidence: 83%
See 2 more Smart Citations
“…k 3(H) /k 3(D) \ 2.07È1.41 This isotope e †ect can be understood in a similar way as for reactions (1) and (2). Here, the energy barriers (e.g., 0.42 *V a G and 0.59 kcal mol~1 for reaction (3) with H and D respectively, at T \ 0 K) are very important. Transmission coefficients follow an opposite direction (e.g., i 3(H) /i 3(D) \ 0.46È1.00 within the range 150È1000 K) and the mass e †ect is negligible.…”
Section: Variational Transition State Thermal Rate Constantsmentioning
confidence: 83%
“…Therefore, the lowest 2A@ PES allows the correlation of all reactants and products of reactions (1), ( 2) and (3). In symmetry, a C =v 2&`PES correlates to the ground state of reactants and products of reactions ( 1) and ( 2), and two PESs (2&`and 2%) correlate for reaction (3). As it has been found that the HCl 2 (2A@) wavefunction is mostly single-determinantal at all the stationary points of the PES,21 the full unrestricted secondorder (UMP2) method is, in principle, accurate MÔllerÈPlesset enough to be used for this study.…”
Section: Aº Ground Potential Energy Surface a Ab Initio Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The only uncertainty concerns the nascent population of vу8. On the low end, the fast flow reactor studies of Setser 22 and Kaufman 23 found no P 8 -P 10 , while on the high end the pressure-pulse chemiluminescence mapping experiments of Tardy 19 found substantial populations for vϭ8 -9. The presence of at least some P 8 -P 10 is supported by the infrared chemiluminescence studies of Polanyi and Jonathan, who reported minor P 8 -P 10 .…”
Section: Hf Kineticsmentioning
confidence: 98%
“…A possible complication in arrested relaxation experiments is the loss of energy from HF by wall collisions. To minimize this perturbation, Setser and co-workers have recently developed a fast flow reactor for HF chemiluminescence studies [8]. Results of observations with this system have been compared with those obtained in arrested relaxation experiments [9], and the fast flow reactor has been used to survey the reactions of F atoms with the Group III, IV, and V hydrides [I0].…”
Section: Types Of Observationmentioning
confidence: 99%